Uso de un software educativo para mejorar el aprendizaje de matemática en los niños de inicial II de la Unidad Educativa Fiscal “Patria” - Ibáñez Jácome, Soraya Cumandá (2020)
The purpose of this research was to determine the influence of the use of educational software to improve the learning of mathematics; it sought to demonstrate the need to implement technological tools in learning processes that allow for better results in the assimilation of knowledge by students; For this reason, it will carry out innovative processes on the part of teachers when making use of technology in activities within the classroom; This is because technological tools currently have a great influence on society. In order to obtain the necessary information to determine the needs of teachers and students, a quasi-experimental design was carried out having an explanatory, quantitative approach, using a deductive method, which allowed quantifying and explaining the study phenomena; there was a population of 19 boys and girls of the Initial Level II of the Fiscal Patria Educational Unit, 19 parents and 2 teachers, techniques and instruments were applied, such as surveys of parents, interviews with teachers, work sheets (pre test and post test) and educational software.